Does the perceived utility of rubrics boost speaker confidence? A study in business organization courses - Verano-Tacoronte, Domingo; Bolívar-Cruz, Alicia (Journal of Management and Business Education, 2025)
In a real academic context, taking the classroom as a reference, this research analyzes the utility that students on two university degree programs give to a rubric for preparing oral presentations. It also assesses the effect that the rubric utility has on the relationship between confidence as a speaker and self-assessment of oral presentation competence. This research was carried out with a sample of 202 university students of Business Organization subjects from two university degrees: Labour Relations and Human Resource Management and Civil Engineering. In both cases, students were required to give an oral presentation on a topic selected by the teacher. One month before presenting in the classroom, students were asked to complete a questionnaire and were provided with a rubric. Finally, after the oral presentation, each student rated his/her overall performance. To analyse data, component analysis with varimax rotation, correlation analysis and hierarchical regression analysis were applied. The results show the greater the perceived utility of the rubric, the greater the influence of confidence as a speaker on self-assessment of oral presentation performance. The rubric is useful in guiding the preparation of the oral presentation, although it seems that the perception of utility is greater for female students than for male students. From a theoretical perspective, the findings suggest that when students perceive the rubric as a credible and reliable guiding tool, a greater correspondence is observed between their perceived abilities and the grades they assign to themselves. From a practical standpoint, providing opportunities for discussion between students and teachers regarding rubric standards can enhance oral communication skills.